Depicting the Underground River Systems in Karst Mountains of Buayan and Ayah Subdistricts Using GGMPlus Data and Springs Distribution - Agung Wibawa; Siti Fauzatun (Journal of Physics and Its Applications, 2022)
The karst mountain area in Buayan and Ayah subdistricts is a mountainous area that stretches from North to South and ends in the South coast region. In this area, many springs are found which are a source of clean water for residents. The existence of springs in the area is an indicator of the existence of underground rivers flowing under the mountainous area, this is also reinforced by the presence of interconnected caves and the existence of river flows in these caves. Analysis the presence of underground river flows in the Karst mountain area in the study area can be identified by looking at the type of rock formations that dominate the area. The density contrast shown through the residual gravity data also shows changes in rock formations related to the presence of water sources in the study area. GGMPlus data was obtained from forward modeling in order to get a residual map. This study shows that rock formations in the Karst area in the study area conform to the topographical shape.